The Design of Wind Power Plant (WPP) for Conveyor Lighting using Wind Turbine Method - Husodo, Budi Yanto; Silalahi, Lukman Medriavin S; Rizal, Ahmad; Simanjuntak, Imelda Uli Vistalina (International Journal of Electronics and Telecommunications, 2026)
This research addresses the issue of poor Public Street Lighting (PSL) in the Belt Conveyor (BC) tripper area, which causes limited visibility. So, this research proposes the design of a Wind Power Plant (WPP) using the 4-wind turbine method. The purpose of this research is the use of WPP technology for PSL development. The research hypothesis is supported by the local environmental conditions, with an average wind speed of 6.7 m/s. This research was conducted by Vertical Axis Wind Turbine (VAWT). The research test uses simulator software to display the voltage and current outputs, and then the output is compared with the results of direct measurements. There are 3 measurement points, namely the inverter output voltage of 226 VAC, the battery output voltage of 51.18VDC, and the full loading current of 7.48A. Significant results occurred at 400W load, because the reliability time to distribute electrical energy to a normal load took 21.2 minutes until the voltage drop was 48VDC, then 800Watt load for 13.48 minutes, and 1600W load for 7.1 minutes. And it is informed that the battery capacity is 200x4AH. Finally, the power output and system efficiency have succeeded in adding value to the diversification of the plant because the burden for PSL has used WPP as the power supply. Suggestions for potential improvements in future work are to measure the environmental impact, especially CO2 emissions, then the challenge of scaling up energy storage and infrastructure improvements as well as the development of maintenance strategies.